2020
DOI: 10.1055/s-0040-1719101
|View full text |Cite
|
Sign up to set email alerts
|

Burned Ear Reconstruction Using the Combination of an Expanded Postauricular Scar Skin Flap and a Postauricular Fascial Flap

Abstract: The external ear is highly vulnerable to burn injury due to its location and thin integument. Reconstruction of the external ear after burns is a major challenge to undertake, and surgeons face many problems, including excessive scar tissue, poor blood supply, a paucity of available skin, and a high infection rate, when designing an operative plan for patients with postburn auricular deformity. In this article, the authors describe their experience of using an expanded postauricular scar flap combined with a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…Tissue expansion is a good method to overcome the problems mentioned above. 9,14,17 Traditional tissue expansion method was usually applied to enlarge the area of the postauricular skin and make it thinner. However, for patients with poorly elastic skin, especially combined with a relatively large contralateral ear, they always required more skin coverage and long-term expansion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tissue expansion is a good method to overcome the problems mentioned above. 9,14,17 Traditional tissue expansion method was usually applied to enlarge the area of the postauricular skin and make it thinner. However, for patients with poorly elastic skin, especially combined with a relatively large contralateral ear, they always required more skin coverage and long-term expansion.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] The frequency of saline injection is also difficult to control, as too rapid expansion leads to problems in the blood supply of expanded flap, while too slow causes an overly thick capsule and waste of time. 9,13 Furthermore, research showed that complications such as necrosis of the expanded flap and exposure of the tissue expander often occurred in the late expansion period. And in patients with postauricular scars, flap necrosis would be more common, especially in the late period of expansion, and blood supply and skin tension should be carefully monitored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, a W-or V-shaped posterior lobule incision on the remnant ear is an effective way to increase the skin surface area for framework coverage (5-7). However, in cases of tiny remnant ear or anotia, skin that was damaged by previous operation or trauma, poor skin mobility, low position of the hairline, or severe hemifacial microsomia, a tissue expansion procedure was necessary to provide additional hair-free skin to cover the framework (20)(21)(22). Tissue expansion was first applied in auricular reconstruction by Neumann in 1957 (10).…”
Section: Discussionmentioning
confidence: 99%
“…With worldwide efforts of surgeons, expanded skin flap method has been modified and is now widely used to overcome skin inefficiency. [9][10][11][12][13][14][17][18][19][20][21][22][23] Complications came after the increasing use of expansion technique. Chen reported 24 cases of partial necrosis of the expanding postauricular flap, with an incidence of 2.9% of necrosis, which is similar to the current study (3.3%).…”
Section: Discussionmentioning
confidence: 99%